2008
DOI: 10.4049/jimmunol.181.6.3784
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Utilizes SMAD3 to Inhibit CD16-Mediated IFN-γ Production and Antibody-Dependent Cellular Cytotoxicity in Human NK Cells

Abstract: TGF-β can be a potent suppressor of lymphocyte effector cell functions and can mediate these effects via distinct molecular pathways. The role of TGF-β in regulating CD16-mediated NK cell IFN-γ production and antibody-dependent cellular cytotoxicity (ADCC) is unclear, as are the signaling pathways that may be utilized. Treatment of primary human NK cells with TGF-β inhibited IFN-γ production induced by CD16 activation with or without IL-12 or IL-2, and it did so without affecting the phosphorylation/activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
200
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(213 citation statements)
references
References 54 publications
7
200
0
Order By: Relevance
“…28,29 The expression levels of CD16a on the NK92/CD16a cells did not differ remarkably from those on NK cells in PBMCs isolated from healthy volunteers. For these reasons, the use of NK92/CD16a seemed to be appropriate for evaluating ADCC mediated by cetuximab.…”
Section: Discussionmentioning
confidence: 98%
“…28,29 The expression levels of CD16a on the NK92/CD16a cells did not differ remarkably from those on NK cells in PBMCs isolated from healthy volunteers. For these reasons, the use of NK92/CD16a seemed to be appropriate for evaluating ADCC mediated by cetuximab.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, TGF-b could contribute to the immune deficit in CLL. In addition, TGF-b inhibits CD16-mediated IFN-g production and ADCC in human NK cells from healthy donors (48). Thus, in vivo administration of rhIL-15 to CLL patients could activate and expand cytotoxic effectors, as well as inhibit the immunosuppressive effects of TGF-b on NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a KIR mismatch in graft versus tumor direction in any of the donor-recipient pairs tested. Trotta et al showed the importance of TGF-b on the inhibition of IFN-g production and antibody-dependent cellular cytotoxicity in human NK cells [45].…”
Section: Discussionmentioning
confidence: 99%